Superfood smoothies : 100 delicious, energizing & nutrient-dense recipes - Morris, Julie (Chef) (Sterling, 2013)
"Everyone loves smoothies and this is the ultimate smoothie book, written by Julie Morris, author of Superfood Kitchen and a superfood expert! Morris whips up 100 nutrient-rich recipes using the world's most antioxidant-, vitamin- and mineral-packed foods, and offers innovative culinary methods for making your smoothies incredibly nutritious and delicious. Whether you're looking for an energy boost, seeking a gentle cleanse, or just trying to get healthy, you'll be inspired to power up the blender!"--